2010
DOI: 10.1038/ejcn.2010.196
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of the Actiheart activity monitor for measurement of activity energy expenditure in children and adolescents with chronic disease

Abstract: Background/Objectives: The purpose of this study was to develop an activity energy expenditure (AEE) prediction equation for the Actiheart activity monitor for use in children with chronic disease. Subjects/Methods: In total, 63 children, aged 8-18 years with different types of chronic disease (juvenile arthritis, hemophilia, dermatomyositis, neuromuscular disease, cystic fibrosis or congenital heart disease) participated in an activity testing session, which consisted of a resting protocol, working on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…However -it is unlikely that any prediction equation derived from healthy children would provide good accuracy; we have found a significant interaction between accelerometer counts and diagnosis that suggests that the relationship between accelerometer counts and EE is different in children with chronic conditions as compared to healthy controls and when compared to other disease groups (43). As an example, in our previous study we tested the validity of the Actiheart accelerometer in the same population and found that a newly developed prediction equation tended to over-estimate energy expenditure in our chronic disease group (43).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However -it is unlikely that any prediction equation derived from healthy children would provide good accuracy; we have found a significant interaction between accelerometer counts and diagnosis that suggests that the relationship between accelerometer counts and EE is different in children with chronic conditions as compared to healthy controls and when compared to other disease groups (43). As an example, in our previous study we tested the validity of the Actiheart accelerometer in the same population and found that a newly developed prediction equation tended to over-estimate energy expenditure in our chronic disease group (43).…”
Section: Discussionmentioning
confidence: 93%
“…Differences in EE and accelerometer counts could be attributed to factors related to disease pathophysiology, sequelae, and drug treatment (42,43). For example, mechanical efficiency due to joint damage or contractures or muscle atrophy from medication and muscle disuse in JA or JDM (23,42); decreased lung function in CF (36) and disturbed muscle metabolism in IMD as well as deconditioning or poor neuromotor control may explain the differences in patterns of movement and increased energy cost of performing physical activities (8,24).…”
Section: Discussionmentioning
confidence: 99%
“…While many measures of fitness are very stable (reliable), we and others have found that activity questionnaires for children are much less reliable 28 . Accelerometry, an objective measure of activity, has validity issues when applied to children with chronic diseases such as arthritis; this is probably because movement patterns and metabolic expenditure are affected in a variety of ways by illness 29,30 .…”
Section: Rheumatologymentioning
confidence: 99%
“…With the advent of technology, secondary objective methods such as portable heart rate monitors, pedometers, and accelerometers are now increasingly available and have been incorporated into the estimation of TEE in chronically ill patients (18). A combination of accelerometer and heart rate has been shown to provide accurate prediction of the physical activity energy expenditure (PAEE) in children (19,20). Accelerometers use piezoelectric transducers and microprocessors that convert acceleration produced by body movements into a digital signal.…”
Section: Measurement Of Resting Energy Expenditurementioning
confidence: 99%
“…Accelerometers use piezoelectric transducers and microprocessors that convert acceleration produced by body movements into a digital signal. In a recent study by Takken et al (19), a chest mounted, combined-unit was employed in a Dutch cohort of children aged 8 to 18 y, for synchronized heart rate and accelerometer recordings. These variables were then used to derive PAEE using a previously validated formula (20).…”
Section: Measurement Of Resting Energy Expenditurementioning
confidence: 99%